Patient-centred professionalism in pharmacy: values and behaviours. Issue 3 (18th May 2015) - Elvey, Rebecca; Hassell, Karen; Lewis, Penny; Schafheutle, Ellen; Willis, Sarah; Harrison, Stephen
Abstract : Purpose: – Research on patient-centred professionalism in pharmacy is scarce compared with other health professions and in particular with pharmacists early in their careers. The purpose of this paper is to explore patient-centred professionalism in early career pharmacists and to describe reported behaviours. Design/methodology/approach: – This study explored patient-centred professional values and reported behaviours, taking a qualitative approach. In all, 53 early-career pharmacists, pharmacy tutors and pharmacy support staff, practising in community and hospital pharmacy in England took part; the concept of patient-centred professionalism was explored through focus group interviews and the critical incident technique was used to elicit real-life examples of professionalism in practice. Findings: – Triangulation of the data revealed three constructs of pharmacy patient-centred professionalism: being professionally competent, having ethical values and being a good communicator. Research limitations/implications: – It is not known whether our participants' perspectives reflect those of all pharmacists in the early stages of their careers. The data provide meaning for the concept of patient-centred professionalism. The work could be extended by developing a framework for wider application. Patient-centred professionalism in pharmacy needs further investigation from the patient perspective. Practical implications: – The findings have implications for pharmacy practice and education, particularly around increased interaction with patients. Social implications: – The data contribute to a topic of importance to patients and in relation to UK health policy, which allocates more directly clinical roles to pharmacists, which go beyond the dispensing and supply of medicines. Originality/value: – The methods included a novel application of the critical incident technique, which generated empirical evidence on a previously under-researched topic.